2021
DOI: 10.21203/rs.3.rs-427101/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Communication Needs for Improved Uptake of Prep and HIVST Services Among Key Populations in Nigeria: A Mixed-Method Study

Abstract: BackgroundWorld Health Organization (WHO) reports that people who indulge in risky behaviours such as penile-anal sex, unprotected intercourse, multiple sex partners, and use of alcohol and illicit drugs are at risk of HIV/AIDS and have been classified as key populations (KPs). Since the introduction of PrEP and HIVST for the key population groups in Nigeria, government entities and implementing partners have used a range of channels in messaging these essential services across to the target groups – ranging f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Participants attributed low PrEP literacy in their communities (beyond the study context) to having limited access to information on PrEP within their communities. Similar findings have been reported by studies among MSM and other key populations [28][29][30]. Consistent with those previous studies, and as we note above, our participants reported they had little or no knowledge of PrEP prior to joining in the study [31].…”
Section: Discussionsupporting
confidence: 92%
“…Participants attributed low PrEP literacy in their communities (beyond the study context) to having limited access to information on PrEP within their communities. Similar findings have been reported by studies among MSM and other key populations [28][29][30]. Consistent with those previous studies, and as we note above, our participants reported they had little or no knowledge of PrEP prior to joining in the study [31].…”
Section: Discussionsupporting
confidence: 92%